Continued optimization of the MLPCN probe ML071 into highly potent agonists of the hM(1) muscarinic acetylcholine receptor - Melancon, Bruce J. (2012)
This Letter describes the continued optimization of the MLPCN probe molecule ML071. After introducing numerous cyclic constraints and novel substitutions throughout the parent structure, we produced a number of more highly potent agonists of the M(1) mACh receptor. While many novel agonists demonstrated a promising ability to increase soluble APPα release, further characterization indicated they may be functioning as bitopic agonists. These results and the implications of a bitopic mode of action are presented.